Research of selective leaching of zinc from metallurgical dust - Бувалец, Дарья Юрьевна; Капустин, Алексей Евгеньевич; Бутенко, Элеонора Олеговна (Technology audit and production reserves, 2015)
This article discusses the process of liquid-phase extraction of zinc from metallurgical dust and sludges. The main purpose of this study is to investigate the efficacy and selectivity of the transition of zinc and iron from the solid phase into the liquid in the process of dissolution of zinc-containing material. To obtain data on selectivity of acid leaching of zinc were conducted experimental kinetic studies, the reaction products were analyzed by photocolorimetry. As the zinc-containing material were used samples of EAF dust with a high content of zinc oxide. As a result of research we obtained the data on the effectiveness and the selectivity of zinc extraction using an acid of different concentrations, as well as with increasing temperature. It was discovered that the process proceeds in two stages. We associate it with a complex chemical composition of the dust. The speed of zinc extraction in the first stage is much higher than the speed of the further course of process. The selectivity value increases during the dissolution process using a solution of sulfuric acid at a concentration of 0,05-0,1 mol/l. Increasing the concentration of the acid solution, as well as the increase of temperature reduces the selectivity of the zinc extraction. The research results can be used to improve industrial technologies for the utilization metallurgical zinc-containing dust and sludges. Carrying out the process at a low concentration of the acid solution for a longer period of time will allow to achieve high recovery of zinc, while maintaining high selectivity.